Lord Kilbrandon – my grandfather - Heather Shaw (Scottish Journal of Residential Child Care)
The Kilbrandon Lecture Series, gives an opportunity to analyse and debate the impact of the 1964 Kilbrandon Report and its impact on the children's hearing system and other issues that affect children in need of care and protection. The 15th Kilbrandon Lecture was delivered by the First Minister Nicola Sturgeon. In this article, Lord Kilbrandon's granddaughter gives a personal account of her grandfather and family life.